Hyperconserved Elements in Human 5′UTRs Shape Essential Post-transcriptional Regulatory Networks - Zuccotti, Paola; Peroni, Daniele; Potrich, Valentina; Quattrone, Alessandro; Dassi, Erik (Frontiers in Molecular Biosciences, 2020)
Post-transcriptional regulation (PTR) of gene expression is a powerful determinant of cellular phenotypes. The 5' and 3' untranslated regions of the mRNA (UTRs) mediate this role through sequence and secondary structure elements bound by RNA-binding proteins (RBPs) and noncoding RNAs. While functional regions in the 3'UTRs have been extensively studied, the 5'UTRs are still relatively uncharacterized. To fill this gap, we used a computational approach exploiting phylogenetic conservation to identify hyperconserved elements in human 5'UTRs (5'HCEs). Our assumption was that 5'HCEs would represent evolutionarily stable and hence important PTR sites. We identified over 5000 5'HCEs occurring in 10% of human protein-coding genes. These sequence elements are rather short and mostly found in narrowly-spaced clusters. 5’HCEs-containing genes are enriched in essential cellular functions and include 20% of all homeotic genes. Homeotic genes are essential transcriptional regulators, driving body plan and neuromuscular development. However, the role of PTR in their expression is mostly unknown. By integrating computational and experimental approaches we identified RBMX as the initiator RBP of a post-transcriptional cascade regulating many homeotic genes. This work thus establishes 5'HCEs as mediators of essential post-transcriptional regulatory networks.